Influence of health education on students’ academic achievement in biology (2016)
The positive effects of health education and healthy lifestyle on adolescent academic achievement cannot be overemphasized as learning experiences to help students accurately assess the level of risk-taking behaviour among their peers, emphasis on the value of good health that reinforces health enhancing attitudes and beliefs are paramount. Little effort had been made by researchers to examine the influence of health education and healthy lifestyle on students’ academic achievement. This study examined the influence of health education and healthy lifestyle on students' academic achievement in Biology. Seven hundred and twenty (720) students of both sexes participated in the study. Three instruments used in the study are Health Education Efficiency Questionnaire (r=0.89), Adolescent Healthy Lifestyle Questionnaire (r=0.94) and Biology Achievement Test (r=0.88). Data was analysed using descriptive of means and standard deviation and inferential statistics of Multiple Regression at p<0.05. The result showed that three independent variables were found to have significant relative contribution on students' achievement. Health Education, β = 0.097, t(715) = 2.102, p<0.05, Risk Behaviour,, β = 0.011, t (715) = 0.241, p<0.05 and Value for good Health, β = 0.138, t (715), = 3.843, p<0.05. It is therefore recommended that health education should be made mandatory for all students in secondary school to enable them form and develop a healthy lifestyle